An optofluidic planar microreactor with photoactive Cu2O/Mo2C/TiO2 heterostructures for enhanced visible light-driven CO2 conversion to methanol. (January 2023) - Merino-Garcia, Ivan; García, Gonzalo; Hernández, Ignacio; Albo, Jonathan
Abstract: Mixing TiO2 with Mo2 C has recently been proposed to improve the photocatalytic conversion of CO2 to methanol under visible light irradiation, although further efforts are still needed to enhance process performance. In this context, the use of p-type semiconductors (i.e ., Cu2 O) in co-doping strategies can enhance not only the redistribution of electric charges due to its narrowing bandgap, but also the selectivity of the reaction towards methanol. This work focuses on the development of a continuous visible light-driven CO2 photoconversion to methanol process in an optofluidic microreactor using Cu2 O/Mo2 C/TiO2 heterostructures. A significant improvement in process performance can be seen under visible light with the heterostructures containing 4 wt% of Cu2 O. Superior methanol production rates (36.3 µmol∙g −1 ∙h −1 ) with an apparent quantum yield = 0.64% and a reaction selectivity = 0.93 are reached, in comparison with the results achieved at Cu2 O-free Mo2 C/TiO2 photocatalytic surfaces (11.8 µmol∙g −1 ∙h −1, 0.21% and 0.92, respectively). This can be adscribed to the role of Cu2 O in the selectivity of the reaction towards methanol. The synergetic effect between Cu2 O, Mo2 C, and TiO2 in the heterostructures may also provoke a more efficient charge separation and transfer, while enhancing the visible light absorption properties of the material and its photocatalytic stability. The maximum methanol rate outperforms most of the values previously reported in slurry batch reactors and evidences the possibility of enhancing the continuous visible light-driven CO2 -to-methanol photoconversion process with efficient metal co-doping approaches in optofluidic microreactors. Graphical Abstract: ga1 Highlights: Efficient optofluidic microreactor with improved surface-area-to-volume ratio. Active Cu2 O/Mo2 C/TiO2 heterostructures for CO2 photoreduction to CH3 OH. Cu2 O ( p-type ) presence leads to enhanced CH3 OH production under visible light. Optimum Cu2 O co-doping of 4 wt% in the Cu2 O/Mo2 C/TiO2 heterostructures. Stable CH3 OH yield after 7 h of continuous operation in the optofluidic reactor.